Research to support evidence-informed decisions on optimizing gender equity in health workforce policy and planning - Neeru Gupta (BMC, 2019)
Abstract Women constitute 70% of the global health and social care workforce, but important knowledge gaps persist to effectively support decision making to optimize gender equity. In this Editorial introducing a new thematic series on 'Research to support evidence-informed decisions on optimizing gender equity in health workforce policy and planning,' we are calling for submissions focusing on research concerning the monitoring, evaluation and accountability of human resources for health policy options through a gender equity lens. We are particularly interested to receive manuscripts advancing the innovative use of data and methodologies in the areas of occupational segregation, decent work, gender pay gap and gendered leadership in the health workforce that could be reproducible across different country contexts.